Bus interdiction efforts by the police:United States v. Drayton - Hughes, Thomas W. (American journal of criminal justice, 2003)
The Supreme Court recently addressed the constitutionality of police interdiction efforts when conducting bus sweeps. The Court held that law enforcement officers are not required by the Fourth Amendment to “advise bus passengers of their right not to cooperate and to refuse consent to searches” (U.S. v. Drayton, 2002, p. 2107). The decision may have implications for how the judicial branch will balance the needs of law enforcement against citizen freedoms in the post-September 11th era. This article explores the surrounding legal issues, the case opinion, and policy implications of this case.